Website Based Academic Information System Design Using Extreme Programming Method - Prasetyo, Deni; Utami, Annisaa; Laksana, Tri Ginanjar (Journal of INISTA, 2024)
SMP Negeri 3 Watukumpul is a junior high school located in Bongas Village, Watukumpul District, Pemalang Regency, Central Java. This school has implemented website-based technology as a medium for conveying information, but the website is no longer usable. The data obtained from the interview results indicate the need for an academic information system website as a medium for disseminating information and managing academic data digitally. Based on the existing problems, researchers will re-create a website-based Academic Information System for SMP Negeri 3 Watukumpul as a medium for delivering information and managing academic data. This research uses the Extreme Programming method, which is one of the development methodologies of Agile Software Development Methodologies. The Extreme Programming method has several stages: Planning, Design, Coding, and Testing. The system uses black box testing on student, admin, and teacher accounts. Blackbox testing on student accounts includes login, register, profile, news, wall magazine, course material, grades, contacts, and logout menus. Blackbox testing on teacher accounts consists of login menus, course materials, grades, and grade page details. Black box testing on admin accounts consists of login menus, school profiles, teachers and employees, news, wall magazines, extracurriculars, and lesson schedules. In testing this system, researchers use black box testing to test its functionality. The black box test from the student's account got a result of 100%, the black box test result from the teacher's account got 100%, and the black box test from the admin account was 98.57%. Thus, the average black box test result from the three users was 99.52%. With the existence of this school website, it is hoped that information dissemination activities and academic data management activities will become more effective and efficient.